The Site of the House of St Mary of Mountjoy, near Jerusalem - Pringle, Denys; Ḳedar, Binyamin Zeʾev 1938- (2022)
This paper attempts to resolve the question of the precise location of the headquarters of the Spanish military order of Mountjoy, which its leader, Rodrigo Álvarez, former count of Sarria (León), began to build beside the Nāblus road at Mountjoy north of Jerusalem in 1178. Although previous studies have mostly agreed in identifying Mountjoy itself with the ridge known as Ra's al-Mashārif from which pilgrims approaching Jerusalem from the north obtained their first view of the city, suggestions for the location of the order’s house have shifted between Shu'fāt, Tall al-Nasba and Tall al-Fūl. Re-examination of the documentary sources and topographical evidence, however, suggests that the house was established on Ra's al-Mashārif itself, beside an existing chapel belonging to the Patriarch of Jerusalem and referred to in the sources as the tolus patriarche.
Cet article tente de résoudre la question de l’emplacement précis du quartier général de l’ordre militaire espagnol de Montjoie, que son chef, Rodrigo Álvarez, ancien comte de Sarria (León), a commencé à construire le long de la route de Nāblus à Montjoie au nord de Jérusalem en 1178. Bien que les études précédentes se soient majoritairement accordées pour identifier Montjoie lui-même avec la crête connue sous le nom de Ra's al-Mashārif d’où les pèlerins approchant de Jérusalem par le nord bénéficiaient de leur première vue de la ville, les suggestions pour l’emplacement de la maison de l’ordre se sont déplacées entre Shu'fāt, Tall al-Nasba et Tall al-Fūl. Le réexamen des sources documentaires et des preuves topographiques suggère toutefois que la maison a été établie sur Ra's al-Mashārif même, à côté d’une chapelle existante appartenant au Patriarche de Jérusalem et désignée dans les sources comme le .